Stress, Depression and Coping in Tuberculosis Patients- A Hospital Based Study - Harikrishna Rajeev; Pradeep Tarikere Satyanarayana (Medsci Publications, 2022)
Background: Tuberculosis (TB) often leaves its impact physically, socially and mentally on patients. Coping strategies refer to the specific efforts, both behavioural and psychological, that people employ to master, tolerate, reduce or minimize stressful events. The study was started to find out the prevalence of Depression in Tuberculosis patients, to find out the effect of Stress and Depression on Coping strategies in patients diagnosed with Tuberculosis. Methodology: The study was a Cross sectional study carried out for period of two years from January 2020 till December 2021. Study was done at District tuberculosis center, SNR Hospital, Kolar. Sample size calculated as 288 based on previous literature search. All data entered in Microsoft office excel sheet, analyzed using SPSS v 22(IBM Corp, USA). Descriptive statistics applied where ever needed and to compare between groups t-test, ANOVA was used and to check for association between factors Chi-square applied. Results: Out of 302 Tuberculosis patients, 29.1% belonged to 41-50 years, 72.2% belonged to Male gender, 77.5% resided in rural area, 24.5% were unemployed, 4% had HIV comorbidity, 46.4% had Diabetes Mellitus. 54.3% had Moderate Depression. Age, Gender, HIV status, Diabetes status, Tb Patients who Perceived TB stigma, BMI, Perceived Family Support, type of family and occupation were few Clinico-social factors which were statistically significant for Perceived stress scores. Conclusion: Tuberculosis is chronic infectious disease where mental health evaluation is neglected, Better management of these psychiatric morbidities should be educated by the treating primary health care doctors and DOTS providers which will have direct or indirect impact on improving treatment adherence, illness perception and patient coping skills.